ATTITUDES OF POLISH SCHOOLS’ TEACHERS TOWARDS THE IDEA OF INCLUSIVE EDUCATION FOR DISABLED PEOPLE - Czyż, Anna Katarzyna (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of the presented research is to determine the direction of teachers’ attitudes towards inclusive education in the context of selected variables. To propagate the idea of inclusion, we need a multi-faceted diagnosis including the diagnosis of teachers’ attitudes, which are responsible for its implementation.The appropriate study was conducted on a sample of 363 teachers. The diagnostic survey was used together with the tool constructed for this study – The Scale for Measuring Attitudes towards Inclusive Education. The tool was subjected to standardization procedures, high reliability (Cronbach’s alpha = 0.85) and theoretical accuracy of the scale was obtained. The attitude analysis was based on the following variables: seniority (work experience in years) and the position (teachers of regular subjects or teacher-psychologist/pedagogue). Considering the tool’s ability, sample size and normality of decomposition, parametric statistics were used to determine the relationships. The results of research show no significance relationship between direction of attitude and position of work and significance relation between direction of attitude and seniority.The results provide a valuable source of information to identify the causes of slow development of inclusion education in countries with similar education models. They give you the opportunity to determine the direction of change and to introduce appropriate solutions.